The Relationship of Strategic Learning to Strategic Innovation: An Analytical Review - saeed, sarkar ahmed (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2024)
Companies must enhance their strategic management to sustain competitiveness in the contemporary business landscape, which highly emphasizes learning and innovation. The significance of innovation is widely acknowledged and deemed essential. To properly apply this, firms must give priority to strategic learning. This study aims to investigate the impact of strategic learning on strategic innovation inside businesses during the adaptation process. The objective is to determine if strategic learning can effectively enable and propel strategic innovation, resulting in sustained success and a favorable influence on organizational performance. The study employs qualitative methodologies to examine and evaluate 14 papers published from 2013 to 2023. Critical analyses address the deficiency by combining and scrutinizing strategic learning and innovation studies. The study demonstrates that strategic learning and innovation favor organizational performance by facilitating swift adaptation to the business environment and enhancing skills. The learning environment supports the advancement of both product and process development, whereas the innovation environment directly influences the business's overall performance. Corporations should encourage ongoing education, implement skills enhancement initiatives, and offer rewards to encourage the adoption of innovative practices. Allocating resources toward developing learning and innovation capacities is warranted, particularly under circumstances characterized by unpredictability.